Climatic effect of light-absorbing impurities on snow : experimental and field observations - Svensson, Jonas (Finnish Meteorological Institute, 2017)
Snow and ice are essential components of the Earth system, modulating the energy budget by reflecting sunlight back into the atmosphere, and through its importance in the hydrological cycle by being a reservoir for fresh water. Light-absorbing impurities (LAI), such as black carbon (BC) and mineral dust (MD), have a unique role in influencing the reflectance of the cryosphere. Deposition of the anthropogenic and natural LAI constituents onto these bright surfaces initiates powerful albedo feedbacks that will accelerate melt. This is important globally, but especially for regions such as the Arctic and the Himalaya. In this thesis, observations from both ambient and laboratory experiments are presented. The overarching research goal has been to better understand the climatic effect of LAI on snow. More specifically, an emphasis has been placed on exploring the process-level interactions between LAI and snow, which will enable better comprehension of LAI affecting the cryosphere. Key findings in this thesis involves the investigations on the horizontal variability of BC concentrations in the surface snow that indicate a larger variability on the order of meter scale at a pristine Arctic site compared to a polluted site nearby a major urban area. In outdoor experiments, where LAI were used to artificially dope natural snow surfaces, the snow albedo was observed to decrease following LAI deposition. The albedo decrease was on the same order as in situ measurements of LAI and albedo conducted elsewhere. As snow melted during the experiment, the snow density was observed to decrease with increasing LAI concentration, while this effect was not observed in non-melting snow. The water retention capacity in melting snow is likely to be decreased by the presence of LAI. Measurements examining the absorption of BC indicate that BC particles in the snow have less absorbing potential compared to BC particles generated in the laboratory. The LAI content of snow pit investigations from two glaciers in the Sunderdhunga valley, ...